Endoscopic submucosal dissection of colitis-related dysplasia - Suzuki, Noriko; Toyonaga, Takashi; East, James E. (Endoscopy, 2017)
Background and study aims Endoscopic submucosal dissection (ESD) offers en bloc resection of lesions, allowing precise pathological assessment. Although possible in ulcerative colitis (UC) patients, the chronic inflammation may increase the procedural risks and reduce the complete resection rate. The aim of this study was to assess the feasibility of ESD for UC and to consider the factors contributing to its technical difficulty.Patients and methods Multicenter experiences of ESD for UC were retrospectively analyzed by reviewing endoscopic videos, pictures, reports, and clinical notes.Results A total of 32 dysplastic lesions were included (23 in British patients, 9 in Japanese patients). The lesions were macroscopically flat or with subtle extension macroscopically in 30 patients (94 %), with a median size of 33 mm (range 12 – 73 mm), and were located in the distal colon, including one on a pouch anastomosis. Submucosal fibrosis and adipose deposition were observed in 31 (97 %) and 13 lesions (41 %), respectively. En bloc resection was possible in 29/32 lesions (91 %). One patient had delayed bleeding. Advanced pathology was observed in 11 lesions (35 %). Recurrence was observed in only one patient (after a median of 33 months [range 6 – 76 months]); however, three patients developed metachronous lesions. Conclusions ESD is feasible for UC dysplasia without an increased rate of complications. Submucosal fibrosis and fat deposition were frequently observed and contributed to the technical complexity. Careful and intensive follow-up should be organized to detect metachronous lesions.